ChemInform Abstract: Trifluoromethylation of α‐Haloketones. Issue 13 (18th March 2013) - Novak, Petr; Lishchynskyi, Anton; Grushin, Vladimir V.
Abstract This method employs only low‐cost chemicals and provides the first nucleophilic trifluoromethylation of α‐bromo‐ketones.